'Semi official' quarterly national accounts - Clarke, Christopher Martin ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Demonstrates that while the compilation of quarterly national accounts is not a trivial exercise, most of the data required is readily available, and is collected, compiled and presented in the routine publications issued by most regional central banks.